HADIS, GERAKAN & POLITIK KEAGAMAAN: MENELAAH PERGESERAN PERAN ULAMA DALAM PEMILUATAS KH. MA’RUF AMIN - Nur Laili Nabilah Nazahah Najiyah; Siska Sukmawati (Jurnal Prodi Ilmu Politik, 2023)
The involvement of ulama during elections is increasingly not only giving lectures, impressions and advice, but also providing "direct" positive support to leaders. In today's election issues can be seen increasingly experiencing a shift. For example, in the 2019 presidential elections, KH. Ma'ruf Amin as vice president. In particular, there are three formulations of the problem, namely: first, what is the role of the ulama during elections in Indonesia and its correlation with hadith? second, what is the profile and track record of KH. Ma'ruf Amin? third, what is the shape of the shift in the involvement of the clergy in the 2019 presidential elections? This paper uses qualitative research methods based on data sources obtained from books, journals, theses and media sites related to the same theme. In analyzing the research data, the researcher carried out three activities, namely data condensation, data presentation, and conclusion/verification which took place simultaneously. The results are, first, the role of the Ulama in bringing prosperity to the nation begins to roll in the presidential elections thus encouraging the political elite to "approach" the Ulama in order to form a "religious" image. Second, before serving as Vice President of the Republic of Indonesia, Ma'ruf Amin was a scholar with the positions of General Chair of the MUI and Executive Board of Nadhatul Ulama (PBNU). Third, the shift in the role of the ulema then went up one level when one of the Indonesian Islamic leaders, namely KH. Ma'ruf Amin was nominated as Joko Widodo's running mate in the 2019 presidential elections. During his candidacy, he also conveyed to santri in Indonesia that ulama can also be leaders.